2017
DOI: 10.1007/s11266-017-9885-6
|View full text |Cite
|
Sign up to set email alerts
|

‘Is My Volunteer Job Not Real Work?’ The Experiences of Migrant Women with Finding Employment Through Volunteer Work

Abstract: We examine whether, and under which conditions, volunteering contributes to migrant integration. We identify two main goals of workfare volunteering-empowerment and employability-which build on two distinct images of the ideal citizen: the empowered citizen and the worker-citizen. Life story interviews were held with 46 first-and second-generation migrant women from Turkey, Morocco and Suriname living in the Netherlands. We found that volunteering contributes to employability and empowerment. However, for two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 34 publications
2
22
0
2
Order By: Relevance
“…Their assumed previous weaknesses, such as the challenges they faced in learning the Finnish language or being unemployed, became their strengths as expert migrants helping other migrants in peer groups (cf. Hokkanen, 2003;Slootjes & Kampen, 2017).…”
Section: Empowered Experiential Experts As Alienated Teachersmentioning
confidence: 99%
“…Their assumed previous weaknesses, such as the challenges they faced in learning the Finnish language or being unemployed, became their strengths as expert migrants helping other migrants in peer groups (cf. Hokkanen, 2003;Slootjes & Kampen, 2017).…”
Section: Empowered Experiential Experts As Alienated Teachersmentioning
confidence: 99%
“…Maahanmuuttajanaisten kotoutumista tutkinut Saraleena Aarnitaival (2012, 181-184) korostaa maahanmuuttajien voimaantumisessa osallisuutta, jossa tiedon saaminen ja jakaminen sekä kokemus omasta tarpeellisuudesta yhteisölle kietoutuvat yhteen. Maahanmuuttajien odotetaan voivan muuttua palvelujen käyttäjistä niiden tarjoajiksi, kunhan he saavat tietoa, jonka avulla he voivat tukea muita tai kykenevät kääntämään heikkoutensa vahvuuksiksi (Handy & Greenspan 2009, 969;Slootjes & Kampen 2017, 1910. Vapaaehtoistoiminta voi tarjota maahanmuuttajille lisäksi uusia rooleja, pääsyn työmarkkinoille tai yhteiskunnalliseen osallisuuteen (Khvorostianov & Remennick 2017, 345;Kosic 2007, 21;Schedler & Glastra 2000, 61).…”
Section: Vertaisuus Aikuiskasvatuksenunclassified
“…Koulutuksen jälkeen ohjaajien odotettiin omaksuvan ohjausammattilaisten kaltaisen auttajan roolin, jossa heidän aiemmat heikkoutensa, kuten vaikeudet oppia suomen kieltä tai työllistyä, kääntyivät vahvuuksiksi: vertaisryhmissä he voisivat käyttää näitä vahvuuksiaan lähtökohtana auttaessaan muita maahanmuuttajia (vrt. Handy & Greenspan 2009;Slootjes & Kampen 2017). Samaistumista kouluttajiin ilmentää se, että vapaaehtoisuudesta huolimatta työelämäohjaajat kuvasivat ohjaavansa vertaisryhmiä "työkseen".…”
Section: Voimaantuneesta Kokemusasiantuntijuudesta Etääntyneeseen Opeunclassified
“…Another qualitative study found that individuals from various ethnic backgrounds indicated that an understanding listening ear, small acts of practical support, and advice from social relations contributed to the ability to continue working despite arising health problems (Qureshi et al 2014). Moreover, in interviews with Turkish and Moroccan women suffering from health problems, Slootjes and colleagues found that social support is an important factor in enabling first-and second-generation migrant women to remain working despite their health problems (Slootjes and Kampen 2017;Slootjes et al 2018).…”
Section: The Protective Effect Of Close Social Tiesmentioning
confidence: 99%